Study on Degradation of Polycarbonate Resin by Glycolysis in Microwave Reactor - Nguyen, Anh Vu; Nguyen, Duc Quang; Vu, Ninh; Nguyen, Thi Ha Hanh (Old Journal, 2017)
In this study, glycolysis process of polycarbonate (PC) resin was researched to recovery Bisphenol-A (BPA) by using Glycerol. The microwave reactor was used to decrease the reaction time. The sodium and potassium hydroxide with different concentrations were carried out for the evaluation of PC conversion and BPA yield. The result showed clearly high efficiency of using microwave on comparison with normal process, with the conversion of PC and yield of BPA reached 100% and 95% respectively within only 5 minutes. This result has shown the application ability of BPA recycling from waste of PC in electronic, medical and transportation vehicle waste.